Clinical value of the HATCH score for predicting adverse outcomes in patients with heart failure. (4th February 2022) - Shibata, N; Kondo, T; Morimoto, R; Kazama, S; Sawamura, A; Nishiyama, I; Kato, T; Hiraiwa, H; Okumura, T; Murohara, T
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The HATCH score is employed as a risk assessment tool for atrial fibrillation (AF) development. However,  the impact of the HATCH score on the long-term adverse outcomes in patients with acute heart failure (AHF) is unknown. Aimes To investigate the clinical value of the HATCH score in AHF. Methods: From a multicenter AHF registry, we retrospectively evaluated 1, 543 consecutive patients admitted with AHF (median age, 78 [69–85] years; 42.3% women) from 2012 to 2019. These patients were divided into five groups based on their HATCH score at admission (scores 0, 1, 2, 3, and 4–7). The correlation between the HATCH score and composite outcome, including all-cause mortality and re-hospitalization due to HF, was analyzed using Kaplan-Meier and Cox proportional-hazard analyses. Results: The median HATCH score was 2 [1-3]. During the follow-up period (median, 16.8 months), the composite endpoint occurred in 691 patients (44.8%), including 416 (27%) patients who died and 455 (29.5%) patients requiring re-hospitalizations due to HF. The Kaplan-Meier analysis showed a significant increase in the composite endpoint with increasing HATCH score (log-rank, p < 0.001). The multivariate Cox regression model revealed that the HATCH score was an independent predictor of the composite endpoint (hazard ratio [HR] 1.181; 95% confidence interval [CI]: 1.111–1.255; p < 0.001) with all-cause mortality (HR 1.153, 95% CI: 1.065–1.249; p < 0.001) and re-hospitalizations due to HF (HR 1.21; 95% CI: 1.124–1.303; p < 0.001) in patients with AHF. Conclusions: The HATCH score is an independent predictor of adverse outcomes in patients with AHF.